2018
DOI: 10.1016/j.neuropsychologia.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Basal forebrain cholinergic system volume is associated with general cognitive ability in the elderly

Abstract: Our results extend previous study findings on BFCS volume associations with cognition in elderly subjects. Despite the observed associations of BFCS volume and cognitive performance, this association seems to reflect a more general association of brain volume and cognition. Accordingly, a specific association of BFCS volume and cognition in non-demented elderly subjects is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…The basal forebrain cholinergic system and its volume (BFCSV) has been suggested to be linked with general cognitive function [20] and the onset of MCI and dementia. However, Heinrich et ] in a metaanalysis of nine studies.…”
Section: Brain Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The basal forebrain cholinergic system and its volume (BFCSV) has been suggested to be linked with general cognitive function [20] and the onset of MCI and dementia. However, Heinrich et ] in a metaanalysis of nine studies.…”
Section: Brain Morphologymentioning
confidence: 99%
“…The basal forebrain cholinergic system and its volume (BFCSV) has been suggested to be linked with general cognitive function [20] and the onset of MCI and dementia. However, Heinrich et al [12 ▪▪ ] found no association between BFCSV and preexisting NCD before surgery, suggesting that cognitive function depends on other relevant factors such as age, education and comorbidities besides BFCSV.…”
Section: Brain Morphologymentioning
confidence: 99%
“…Six neuropsychological tests with a total of eight outcome measures were administered once at enrolment (T0) and again in identical form at 7 days (T1), and 3 months (T2) ( Table 1) [19]. Four tests were part of the Cambridge Neuropsychological Test Automated Battery (CANTAB; CANTAB Research Suite, Cambridge Cognition Ltd., UK) and were performed on touch-screen electronic devices with a press pad.…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…The battery consisted of 6 age-sensitive neuropsychological tests of which 4 (Paired Associates Learning; Verbal Recognition Memory; Spatial Span; Simple Reaction Time) were part of the CANTAB computerized battery and tapped the cognitive domains visual memory, verbal memory, working memory, and processing speed. Full details of the cognitive tests and testing procedure can be found elsewhere [20]. Two paper-pencil tests, Trail-Making Test-B and Grooved Pegboard, measuring executive function and fine motor skills, respectively, supplemented the battery.…”
Section: Cognitive Assessmentmentioning
confidence: 99%